First results of the tracking system calibration of the TAIGA-IACT telescope. (February 2019) - Zhurov, D.; Gress, O.; Sidorov, D.; Astapov, I.; Bezyazeekov, P.; Boreyko, V.; Borodin, A.; Budnev, N.; Brueckner, M.; Chiavassa, A.; Dyachok, A.; Fedorov, O.; et al.
Abstract: In TAIGA Observatory (Tunka Advanced Instrument for cosmic ray physics and Gamma-ray Astronomy) we are commissioning the first Imaging Atmospheric Cherenkov Telescope (IACT). The telescope has an alt-azimuth mount and 17-bit shaft encoder for each axis, stepper motors are used for axis control. For the pointing calibration of the telescope a CCD-camera is installed on the dish of the telescope and its position allows to capture simultaneously both the Cherenkov camera with LEDs and the sky with observed source. Since October 2017, the telescope has been operating in tracking mode. In this work the TAIGAIACT telescope pointing calibration approach and first results of the tracking operations are described.